The Burden of Mental Illness Among Veterans: Use of VHA Health Care Services by Those With Service-connected Conditions - Maynard, Charles; Batten, Adam; Liu, Chuan-Fen; Nelson, Karin; Fihn, Stephan D (Medical care, 2017)
Little is known about how Veterans with service-connected conditions use health care provided by the Veterans Health Administration (VHA). To ascertain what proportion of Veterans with service-connected conditions used VHA health care and whether it varied according to type of condition, combined disability rating, age, sex, military rank, or other characteristics and whether there were differences in receipt of inpatient and outpatient care. Cross-sectional analysis of administrative benefits and claims data for 2015 and 2016. In total, 4,029,672 Veterans who had an active award status for service-connected conditions in October 2016. Independent variables included age, sex, military rank, service branch, combined disability rating, Agent Orange exposure, and type of service-connected condition. The key-dependent variable was VHA health care use including specific types of health care utilization such as inpatient and outpatient services. In total, 52% of those with service-connected conditions used VHA health care. Type of condition and disability rating were associated with use. Over 65% of those with major depression, posttraumatic stress disorder (PTSD), Agent Orange exposure, or diabetes used VHA health care, as did 76% of those with a 100% rating. Almost one third of users of VHA health care were compensated for PTSD. In general, both inpatient and outpatient mental health services were frequently used by Veterans with service-connected mental health conditions. Veterans with service-connected conditions, particularly those with diabetes or mental illness such as depression or PTSD, depend heavily upon VHA for health care, including mental health services.